2015
DOI: 10.1097/cin.0000000000000193
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Simulation Scenario and Evaluation Checklist for Patients With Asthma in Emergency Care

Abstract: Care for patients with asthma requires prompt and effective decision-making abilities. Many nursing students report a lack of preparedness and competence with respect to their ability to perform nursing duties. Simulation-based learning has been developed as a potential solution to this problem. Moreover, the simulation scenario with an evaluation checklist offers a reliable evaluation strategy for the education and training of clinical decision-making skills among nursing students. The simulation scenario and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Lee et al [31] found in their study conducted on nursing students using a simulation scenario prepared for a patient with asthma that students' problem solving and clinical decision making skills developed and patient safety improved through developed simulation scenarios and evaluation checklists. In a review study conducted by D'Souza et al [18] of 45 published works that students became skillful at clinical decision making and performing applications, and it was recommended that a simulation scenario should also be prepared for different cases.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [31] found in their study conducted on nursing students using a simulation scenario prepared for a patient with asthma that students' problem solving and clinical decision making skills developed and patient safety improved through developed simulation scenarios and evaluation checklists. In a review study conducted by D'Souza et al [18] of 45 published works that students became skillful at clinical decision making and performing applications, and it was recommended that a simulation scenario should also be prepared for different cases.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, decision making skill is a high-level skill that is difficult to assess [26]. Patient care compels timely and successful decision-making capabilities [4]. Such skill is essential to recognize and intervene the patient whose state is declining [27].…”
Section: Decision-making As An Important Clinical Skill For Undergraduate Nursing Studentsmentioning
confidence: 99%
“…[3] Numerous nursing students reported a deficiency of vigilance and competency with respect to their capacity to achieve nursing responsibilities. [4] In this connection, nurse educators have recognized that several nursing students have inconvenience in performing decision-making in clinical practice. [5] Thus, caring for patients requires prompt and effective decisionmaking abilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have even cited that nursing graduates are not capable and not displaying clinical skills competency in the clinical areas during the clinical practicum [8]. Numerous nursing students reported a deficiency of clinical performance and competency with respect to their capacity to achieve nursing responsibilities [9]. Furthermore, there had been limited studies about the capability to utilize scientific information for clinical nursing decision-making.…”
Section: Introductionmentioning
confidence: 99%